OLIVER TWIST - Dickens, Charles, 1812-1870.; Tavner, Gill; Donnelly, Karen (Berkshire, U.K. : Baker Street Press, 2018)
"Bah, humbug! Fools wishing me a Merry Christmas should be forced to sit on cushions stuffed with holly leaves or boiled with their own Christmas puddings." Miserable old miser Ebenezer Scrooge hates Christmas.
Keywords: Children's stories, English; English fiction